Early removal of indwelling urinary catheters in children undergoing abdominal tumor resection with epidural analgesia - Shachi Srivatsa; Jennifer H. Aldrink; Dana Schwartz; Grant Heydinger; Andrew Davidoff; Andrew J. Murphy; Kyle O. Rove; Sara A. Mansfield (Journal of Pediatric Surgery Open)
Purpose: Epidural analgesia (EA) is commonly employed for postoperative pain management in children undergoing abdominal tumor resection. Indwelling urinary catheters (IUCs) often remain for the duration of EA administration due to concern for associated urinary retention. This study focuses on children undergoing abdominal tumor resection with appropriate EA coverage, to assess whether IUC can be removed early with minimal risk of reinsertion for urinary retention. Methods: A retrospective review of children who underwent abdominal tumor resections with EA between 2015 and 2023 at two institutions was conducted. Data were summarized, and rates of postoperative urinary retention requiring catheter reinsertion and catheter-associated urinary tract infections (CAUTIs) were compared between patients with early and late IUC removal groups using Fisher's exact testing. “Early” was defined as IUC removal with EA in place and “late” as IUC removal after or concurrent with EA discontinuation. Results: A total of 228 children underwent abdominal tumor resections with EA. Of these, 104 had early, and 124 had late IUC removal. The average postoperative day (POD) of IUC removal in the early group was 1.1±0.5 days and 2.9±1.1 days in the late group. EA was at T12 level or higher in 101 patients (97.1 %) in the early group, and 68 (54.8 %) in the late group (p<0.001). EA contained opioids in 27 (26.0 %) in the early group and 54 (43.5 %) in the late group (p=0.005). There were 6 (5.8 %) children in the early group and 1 (0.8 %) in the late group requiring re-catheterization (p = 0.049). For those requiring re-catheterization, the EA level was T7-8 in 5 patients, T10-11 in 1 patient, and T4 in 1 patient (late). There was 1 (1.0 %) patient with a CAUTI in the early group, and 3 (2.4 %) patients in the late group (p = 0.63). Conclusions: Early removal of indwelling urinary catheters in the setting of thoracic epidural analgesia is associated with a small risk of urinary retention necessitating catheter re-insertion. Balancing the need for IUCs with this possibility, patient comfort, and infectious risk should inform decision-making to best align with enhanced recovery efforts.